A formação sindical no Brasil nos anos 80: concepções e práticas - Portela, Laélia Gurgel (1990)
The aim oh this work is to offer a view oh the Syndical Education in Brazil, since the last of the 80's, showing the emergence oh a new kind of education for : syndicalists that outlines - in its major trend - a political formation of the worker class.